The fortresses of Ukraine. The builders of early iron age strongholds in Podolia - Ignaczak, Marcin; Boltryk, Yuriy; Shelekhan, Oleksandr; Lifantii, Oksana; Olędzki, Łukasz (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2016)
The most challenging question regarding the defensive settlements of the Pontic forest ‑steppe is the reason behind their construction at all and size. The most frequent interpretations centre around two questions: were they to protect from external threats (i.e. the nomads) or were they the result of a carefully planned construction strategy related to the economic and social pressure from the Greek colonies in the Black Sea region? it is also possible that both explanations are true.
Ukrainian fortresses a study of a strongholds system from the early iron age in Podolia
Keywords: Black Sea region forest ‑steppe; eastern European forest ‑steppe; fortified settlements; Podolia; Scythian time